Correspondencia entre Ira K. Wells y Roberto H. Todd - Wells, Ira K.; Todd, Roberto H. (My University, 1925)
Carta entre Ira K. Wells y Roberto H. Todd sobre asuntos políticos.
Keywords: Puerto Rico--Politics and government.; Puerto Rico--Política y gobierno.